MAHKAMAH KONSTITUSI DALAM PERSPEKTIF INDEKS DEMOKRASI DAN OTONOMI DAERAH - Inna Junaenah (Komisi Yudisial RI, 2025)
The Constitutional Court (MK) holds a primary role as the guardian of democracy and the constitution. Nevertheless, the MK’s role, as evidenced by its legal reasoning and judgments, has not consistently reflected its function in upholding democratic values. This MK’s strategic role is reflected, among other indicators, in the democracy index published by the Economist Intelligence Unit. The 2022 democracy index report noted that Judgment Number 91/PUU-XVIII/2020 contributed to Indonesia’s 2021 democracy score. However, this assessment was not sustained, as Judgment Number 90/PUU-XXI/2023 subsequently contributed to a decline in Indonesia’s democracy index in 2024. This article adopts a doctrinal legal research methodology, utilizing both case and statutory approaches to analyze the concepts of the democracy index, constitutionalism, and decentralization. The findings highlight two principal aspects. First, an analysis of the interplay between the MK’s judgments and the indicators of the democracy index provides a conceptual framework for understanding the MK’s influence on fluctuations in Indonesia’s democratic score. In this context, MK’s role as the guardian of democracy significantly affects the quality of judicial independence, which serves as an indicator of democracy and democratization at the central government level. Additionally, the enforcement of statutory norms arising from the MK’s judgments further shapes the structure of regional autonomy. Second, from the perspective of regional autonomy, Judgment Number 91/PUU-XVIII/2020 enables greater public participation at the regional level by extending attention to the principle of meaningful participation in the process of regional law-making. On the contrary, Judgment Number 90/PUU-XXI/2023 represents a regression in regional autonomy, as evidenced by the diminished discretion of regional governments to determine local leadership through democratic means and to guarantee equal access for all citizens to stand for public office. Additionally, Judgment Number 90/PUU-XXI/2023 and Number 2/PHPU.PRES-XXII/2024 appears to legitimize dynastic political practices and may further contribute to decreased voter participation. Identifying these implications, these findings underscore the importance of maintaining the MK’s consistency in fulfilling its role as the guardian of democracy and of strengthening public oversight of the MK’s role as part of broader efforts to preserve the integrity of regional autonomy.